IMPLEMENTASI KEBIJAKAN INKLUSIF DALAM PELAYANAN PUBLIK BAGI KELOMPOK RENTAN: KAJIAN PUSTAKA TENTANG AKSESIBILITAS, PARTISIPASI, DAN KEADILAN SOSIAL BAGI PENYANDANG DISABILITAS DAN KELOMPOK MARGINAL - Istiarsyah Istiarsyah; Fauzan Fauzan (ADMIN: Jurnal Administrasi Negara, 2026)
This study aims to analyse the implementation of inclusive policies in public services for vulnerable groups, particularly persons with disabilities and marginalised groups, through a literature review approach. This study departs from the fact that although various regulations have been formulated to ensure equality and inclusiveness, their implementation in the field still faces significant obstacles, both structurally, culturally, and administratively. Using a qualitative analysis method based on thematic synthesis of various scientific sources and national policies, this study examines two main dimensions that determine the success of inclusive policies, namely accessibility and participation, and examines their impact on the achievement of social justice. The results of the study show that physical, digital, and social accessibility are still not optimal in reaching vulnerable groups, while public participation tends to be symbolic without having a substantive influence on policy. Social justice can only be realised if public policy is designed with affirmative action, involves multiple parties, and is accompanied by a paradigm shift in bureaucracy towards adaptive and humanistic governance. Thus, inclusive policies are not only administrative instruments, but also a representation of the state's moral commitment to realising equal, fair, and welfare-oriented public services